ANALYSIS OF THE IMPLEMENTATION OF MIXUE FRANCHISE AGREEMENTS IN CIREBON REGENCY REVIEWED FROM GOVERNMENT REGULATION NO. 42 OF 2007 CONCERNING WARALABA - Salza Hubbillah, Widya; Romlahayati, Yanti; Umar, Jaenudin (Hukum Responsif, 2024)
A franchise agreement is one aspect of legal protection for the parties from acts that harm other parties. An exclusive agreement is an agreement to enter into an exclusive agreement that can result in hindering or hindering other business actors from entering into the same agreement. The purpose of writing this scientific paper is to find out how the implementation of Mixue franchise agreements according to Government Regulation No. 42 of 2007 concerning Franchising and Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. The research method used in this scientific paper uses empirical juridical abbreviations, using primary and secondary data, which are then analyzed using descriptive qualitative analysis. This study's results show that the Mixue franchise agreement implementation in Cirebon Regency is guided by Chapter 5 of Government Regulation No. 42 of 2007 concerning Franchise. However, suppose you look at Chapter 15 of Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition in the Mixue franchise agreement. In that case, some practices cause monopolies and unfair business competition.